Gendered resilience in India’s seaweed farming: Highlighting policy lessons from the COVID-19 pandemic for inclusive Blue economy framework - Sundaram Swathi Lekshmi Perumal; Radhakrishnan Kalidoss; Gopal Nikita; D. Divu; Mojjada Suresh Kumar; V.P. Vipin Kumar; George Saju; S. Surya; R. Narayanakumar; Kingsly Jose; V.A. Leslie; S.S. Arabindoo; et al. (Marine Policy, 2026)

Assessment of microplastics contamination in riverine environments: Urban stretch of Cauvery and Kollidam rivers of southern India - S. Venkatramanan; K. Radhakrishnan; R. Muthuramalingam; K. Sivakumar; T. Kongeswaran; K. Prabakaran; R. Rameshkumar; V. Madavaraj (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Models reveal the importance of alternative hosts and environmental transmission for emergence of bacterial disease in muskoxen in the Arctic - Juan S. Vargas Soto; Marina Reyne; McCaide Wooten; Sreejith Radhakrishnan; Fabien Mavrot; Susan Kutz; Taya Forde; Eric R. Morgan (Ecological Modelling, 2026)

Impact of microbial application on the hardening period and defense signaling activation of micropropagated banana var. Nendran - Reni R Krishna; Maria George; Aswani Ravi; Mary Theresa; Riya Alex; Remakanthan Appukuttan; Radhakrishnan Edayileevettil Krishnankutty (In Vitro Cellular & Developmental Biology - Plant, 2026)

Endophytic Xylaria sp. enhances tolerance in rice to bacterial leaf blight and promotes growth - K. Sushitha; A. Sajeena; N. V. Radhakrishnan; M. Joy; Jacob John; Swapna Alex; R. Beena (European Journal of Plant Pathology, 2025)

Novel o-Terphenyl Luminophores for Optoelectronic Devices: Synthesis, Photophysical, Electrochemical, and Thermal Analysis - Amarsinh R. Mainak; Pranjali S. Kewate; Vasanti B. Shabade; Vishnu V. Kutwade; Radhakrishnan M. Tigote; Netaji K. Desai; Sidram R. Pujari (Journal of Fluorescence, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

First report of stem canker disease caused by Neoscytalidium lignicola on dragon fruit in Kerala - Kovvuri Janakadatta Reddy; M. K. Dhanya; R. Ayisha; A. Sajeena; N. V. Radhakrishnan (Indian Phytopathology, 2025)

Unveiling Hidden Water Resources: Deep Learning and Remote Sensing for Subsurface Hydrology for Environmental Health - Jampani Satish Babu; Dinesh G.; R. Suganya; P. Radhakrishnan; Anand Sutar; Alex David S.; L. Malleswara Rao (Remote Sensing in Earth Systems Sciences, 2025)

In vivo and in silico preliminary evaluation of the cyanobacterial peptides portoamides A and B against the white spot syndrome virus in freshwater crabs (Paratelphusa hydrodomous) - Bharath Raja; Vidya Radhakrishnan; Sudhakaran Raja; Sandra Pereira; Catarina Gonçalves; Vitor Vasconcelos; Mariana Reis; Joana R. Almeida (Aquaculture International, 2025)
White spot syndrome, caused by the white spot syndrome virus (WSSV), is a devastating viral disease responsible for significant economic losses in the shrimp farming industry. In the search for natural therapeutic alternatives against WSSV, this study explored the antiviral potential of portoamides, natural peptides produced by the cyanobacterium Phormidium sp. LEGE 05292. Given that the structural proteins of the viral envelope, specifically VP28, VP26, and VP24, are the primary mediators of host cell attachment, they serve as promising targets for antiviral drug development. Our approach combined in vivo post-infection histopathological analysis with in silico molecular docking to assess the antiviral efficacy of portoamides. In the in vivo study, crabs were injected with portoamides alongside WSSV and monitored for 30 days post-infection. The antiviral activity of portoamides was evaluated through survival rates and histopathological observations. The results revealed that crabs treated with portoamides showed improved survival and reduced signs of viral infection compared to the control group. In parallel, in silico molecular docking analysis was conducted to assess the binding affinity between portoamides and the viral envelope proteins VP28, VP26, and VP24. The docking results demonstrated that these proteins exhibited the highest binding energies with portoamides, indicating a strong interaction that could potentially inhibit viral attachment and replication. Our findings suggest that portoamides effectively inhibit WSSV replication by interacting with the viral envelope proteins, thereby preventing the virus from establishing infection in crabs. Moreover, it is hypothesized that portoamides may stimulate the immune system in crabs, further enhancing resistance to WSSV infection. However, additional studies are needed to fully understand the immunomodulatory mechanisms involved. These preliminary results highlight the potential of portoamides as natural antiviral agents for combating WSSV in aquaculture settings, paving the way for future research on their application in disease management strategies.

Fluorescent N-Doped Carbon Dots as a Biocompatible Sensor for Thiophanate-Methyl Detection - K. Radhakrishnan; R. Suriyaprakash; L. Srimathi Priya; P. Saravanan; Mir Waqas Alam; Pitcheri Rosaiah; Guru Prakash Nunna; Tae Jo Ko (Journal of Fluorescence, 2025)

Performance prediction of emulsion treated base layer mixes using indirect tensile strength and resilient modulus test parameters - Jithin Kurian Andrews; Vishnu Radhakrishnan; Reebu Zachariah Koshy; C. S. R. K. Prasad (Innovative Infrastructure Solutions, 2024)

Novel in-genome based analysis demonstrates the evolution of OmpK37, antimicrobial resistance gene from a potentially pathogenic pandrug resistant Klebsiella pneumoniae MS1 isolated from healthy broiler feces - Sreejith Sreekumaran; Priya V K; Manjusha Premnath; Prathiush P R; Anisha M N; Jyothis Mathew; Jayachandran K; Radhakrishnan E K (Science of The Total Environment, 2024)

Energy efficiency and economics of small-scale fisheries (SSF) in India: A VIKOR based multicriteria decision-making model for sustainable fisheries management - Swathi Lekshmi Perumal Sundaram; Kalidoss Radhakrishnan; R. Narayanakumar; Vipin Kumar V. P; S. Surya; D. Divu; Nikita Gopal; Jose Kingsly; V.A. Leslie; Suresh Kumar Mojjada; Mayur Shivdas Tade; Aarsha Subramanian; et al. (Journal of Cleaner Production, 2024)

Effects of Zinc Oxide Nanoparticles Supplementation on Growth Performance, Meat Quality and Serum Biochemical Parameters in Broiler Chicks - V. Mozhiarasi; R. Karunakaran; P. Raja; L. Radhakrishnan (Biological Trace Element Research, 2024)

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

Synthesis and characterization of gold nanoparticles using Brevibacterium casei (SOSIST-06) isolated from Southern Ocean water samples and their in vitro and in silico anti-WSSV activity - R. Namitha; B. Abirami; B.S. Anoop; D.V. Diya Dominic; Ahna Ameer; K. Manigundan; M. Radhakrishnan; P. Santhiya; Parli V. Bhaskar; K. Govindaraju; I.S. Bright Singh; G. Dharani (Aquaculture, 2024)

Predicting Human Risk with Multidrug Resistant Enterobacter hormaechei MS2 having MCR 9 Gene Isolated from the Feces of Healthy Broiler Through Whole-Genome Sequence-Based Analysis - Sreejith Sreekumaran; Manjusha Premnath; P. R. Prathyush; Jyothis Mathew; Chitra C. Nath; Nimmy Paul; Swapna Susan Abraham; E. K. Radhakrishnan (Current Microbiology, 2024)

Fluorescence Sensor for Water in Organic Solvent Using Graphene Oxide- Rhodamine B and Cucurbit[7]uril - Pavitra Rajendran; Radhakrishnan SathishKannan; Karuppasamy Karpagalakshmi; Lakshminarayanan Piramuthu; Erumaipatty R. Nagarajan; Senthilmurugan Subbiah; Cheng Yang; Narayanan Selvapalam (Journal of Fluorescence, 2023)

Measurement and comparison of photosynthetically active radiation by different methods at Delhi - Humaira Ghayas; S. R. Radhakrishnan; Vinay Kumar Sehgal; Sachchidanand Singh (Theoretical and Applied Climatology, 2022)

Neuroprotective and Proneurogenic Effects of Glucosamine in an Internal Carotid Artery Occlusion Model of Ischemia - Priya Jhelum; Mydhili Radhakrishnan; A. R. Sam Paul; Sandeep K. Dey; Avijeet Kamle; Arvind Kumar; Abhay Sharma; Sumana Chakravarty (NeuroMolecular Medicine, 2022)

Study of variation of aerosol optical properties over a high altitude station in Indian Western Himalayan region, palampur using raman lidar system - Shishir Kumar Singh; S. R. Radhakrishnan; Jaswant; Sumit Kumar Mishra; Devesh Kumar Shukla; Ashish Ranjan; Chhemendra Sharma (Journal of Atmospheric Chemistry, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Promalabaricone B from Myristica fatua Houtt. seeds demonstrate antidiabetic potential by modulating glucose uptake via the upregulation of AMPK in L6 myotubes - B. Prabha; S. Sini; D. R. Sherin; S. Neethu; K. B. Rameshkumar; T. K. Manojkumar; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Quinalphos Tolerant Endophytic Bacillus sp. Fcl1 and its Toxicity-Alleviating Effect in Vigna unguiculata - Silju Juby; Divya Choyikutty; A. R. Nayana; K. Jayachandran; E. K. Radhakrishnan (Current Microbiology, 2021)

Fatty acid desaturase-2 (ahFAD2) mutant alleles in peanut (Arachis hypogaea L.) pre-breeding lines: an insight into the source, features, discourse, and selection of novel pre-breeding lines - J. H. Kamdar; M. D. Jasani; B. C. Ajay; Kirti Rani; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; M. K. Pandey; P. Janila; T. Radhakrishnan; R. K. Varshney; S. K. Bera (Genetic Resources and Crop Evolution, 2021)

Water deficit-induced oxidative stress and differential response in antioxidant enzymes of tolerant and susceptible tea cultivars under field condition - M. Nalina; S. Saroja; M. Chakravarthi; R. Rajkumar; B. Radhakrishnan; K. N. Chandrashekara (Acta Physiologiae Plantarum, 2021)

Spatial accessibility analysis of schools using geospatial techniques - R. Shanmathi Rekha; Nisha Radhakrishnan; Samson Mathew (Spatial Information Research, 2020)

Combined Effect of Pseudomonas spp. Consortium and Fertilizer with Micronutrients on Enhanced yield of Amaranthus tricolor (L.) - S. Soumya; S. Sreejith; K. Shibil Shad; P. Anusha; B. Swathy; R. Renikrishna; S. Saranya; P. Jishma; E. K. Radhakrishnan; A. Remakanthan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Biofilm Changes of Clinically Isolated Coagulase Negative Staphylococci - K. R. Soumya; P. Jishma; Sheela Sugathan; Jyothis Mathew; E. K. Radhakrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Role of Nanocurcumin as a Surface Modifying Agent with Excellent Preventive Effect on Device-Related CoNS Infections - K. R. Soumya; P. Jishma; R. Dhivya; Jamespandi Annaraj; Sheela Sugathan; Jyothis Mathew; E. K. Radhakrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Native bighead carp Hypophthalmichthys nobilis and silver carp Hypophthalmichthys molitrix populations in the Pearl River are threatened by Yangtze River introductions as revealed by mitochondrial DNA - Chao Li; Junjie Wang; Jiaqi Chen; Kevin Schneider; Radhakrishnan K. Veettil; Kathryn R. Elmer; Jun Zhao (Journal of Fish Biology, 2020)
Bighead carp Hypophthalmichthys nobilis and silver carp Hypophthalmichthys molitrix have been two economically important aquaculture species in China for centuries. In the past decades, bighead and silver carp have been introduced from the Yangtze River to many river systems in China, including the Pearl River, in annual, large‐scale, stocking activities to enhance wild fisheries. Nonetheless, few studies have assessed the ecological or genetic impacts of such introductions on native conspecific fish populations. An mtDNA D‐loop segment of 978 bp from 213 bighead carp samples from 9 populations and a 975 bp segment from 204 silver carp samples from 10 populations were obtained to evaluate genetic diversity and population integrity. Results from a haplotype network analysis revealed that most haplotypes of the Pearl River clustered with those of Yangtze River origin and only a small proportion were distinct, suggesting that both the native Pearl River bighead and silver carp populations are currently dominated by genetic material from the Yangtze River. The genetic diversity of Pearl River populations is high in both species because of this inter‐population gene flow, but the diversity of native Pearl River populations is low. To preserve the native genetic diversity, stocking of non‐native fingerlings should cease immediately and native Pearl River bighead and silver carp fish farms should be established. This research demonstrates the danger to native biodiversity across China because of the substantial, ongoing stock‐enhancement activities without prior genetic assessment.

Distribution of multi-virulence factors among Aeromonas spp. isolated from diseased Xiphophorus hellerii - Soumya Das; R. Aswani; B. Jasim; K. S. Sebastian; E. K. Radhakrishnan; Jyothis Mathew (Aquaculture International, 2020)

Psidium guajava Leaf Extracts and Their Quercetin Protect HepG2 Cell Lines Against CCL4 Induced Cytotoxicity - K. Vijayakumar; R. L. Rengarajan; R. Radhakrishnan; Shilu Mathew; Ishtiaq Qadri; A. Vijaya Anand (Indian Journal of Clinical Biochemistry, 2019)

Beneficial Changes in Capsicum frutescens Due to Priming by Plant Probiotic Burkholderia spp. - Rohini Sabu; R. Aswani; K. S. Nidheesh; J.G. Ray; A. Remakanthan; E. K. Radhakrishnan (Probiotics and Antimicrobial Proteins, 2019)

Genotyping-by-sequencing based genetic mapping reveals large number of epistatic interactions for stem rot resistance in groundnut - Sneha M. Dodia; Binal Joshi; Sunil S. Gangurde; Polavakkalipalayam P. Thirumalaisamy; Gyan P. Mishra; Dayama Narandrakumar; Pooja Soni; Arulthambi L. Rathnakumar; Jentilal R. Dobaria; Chandramohan Sangh; Annapurna Chitikineni; Sumitra V. Chanda; et al. (Theoretical and Applied Genetics, 2019)

Plant Growth Promoting Endophytic Serratia sp. ZoB14 Protecting Ginger from Fungal Pathogens - Rohini Sabu; R. Aswani; P. Jishma; B. Jasim; Jyothis Mathew; E. K. Radhakrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Genetics of language and its implications on language interventions - Radhakrishnan Sriganesh; R. Joseph Ponniah (Journal of Genetics, 2018)

Accumulation of Heavy Metals in Some Marine Fisheries Resources Collected from Gulf of Mannar Marine Biosphere Reserve, Southeast Coast of India - S. Rameshkumar; P. Prabhakaran; K. Radhakrishnan; R. Rajaram (Proceedings of the Zoological Society, 2018)

Improving oil quality by altering levels of fatty acids through marker-assisted selection of ahfad2 alleles in peanut (Arachis hypogaea L.) - Sandip K. Bera; Jignesh H. Kamdar; Swati V. Kasundra; Pitabas Dash; Anil K. Maurya; Mital D. Jasani; Ajay B. Chandrashekar; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; Manish K. Pandey; Pasupuleti Janila; et al. (Euphytica, 2018)

Differential Modulation of Endophytic Microbiome of Ginger in the Presence of Beneficial Organisms, Pathogens and Both as Identified by DGGE Analysis - Rohini Sabu; R. Aswani; Priya Prabhakaran; B. Krishnakumar; E. K. Radhakrishnan (Current Microbiology, 2018)

Culturable Endophytic Bacteria of Ginger Rhizome and their Remarkable Multi-trait Plant Growth-Promoting Features - Sabu Rohini; R. Aswani; M. Kannan; V. P. Sylas; E. K. Radhakrishnan (Current Microbiology, 2018)

Studying Land Use Travel Demand Interaction Using 3S Technology for Tiruchirappalli City - Nisha Radhakrishnan; R. Aswathy; Samson Mathew (Journal of the Indian Society of Remote Sensing, 2017)

Development of a multiplex RT-PCR for simultaneous diagnosis of human metapneumovirus (HMPV) and human respiratory syncytial virus (HRSV) from clinical specimens - Seetha Dayakar; Heera R. Pillai; Vineetha P. Thulasi; Radhakrishnan R. Nair (VirusDisease, 2016)

Distinct Bacterial Communities Associated with the Coral Model Aiptasia in Aposymbiotic and Symbiotic States with Symbiodinium - Till Röthig; Rúben M. Costa; Fabia Simona; Sebastian Baumgarten; Ana F. Torres; Anand Radhakrishnan; Manuel Aranda; Christian R. Voolstra (Frontiers in Marine Science, 2016)

Transgenic peanut overexpressing mtlD gene confers enhanced salinity stress tolerance via mannitol accumulation and differential antioxidative responses - Kirankumar G. Patel; Viralkumar B. Mandaliya; Gyan P. Mishra; Jentilal R. Dobaria; Radhakrishnan Thankappan (Acta Physiologiae Plantarum, 2016)

Layer-specific interhemispheric functional connectivity in the somatosensory cortex of rats: resting state electrophysiology and fMRI studies - Kwangyeol Baek; Woo Hyun Shim; Jaeseung Jeong; Harsha Radhakrishnan; Bruce R. Rosen; David Boas; Maria Franceschini; Bharat B. Biswal; Young R. Kim (Brain Structure and Function, 2016)

Upper Airway Elasticity Estimation in Pediatric Down Syndrome Sleep Apnea Patients Using Collapsible Tube Theory - Dhananjay Radhakrishnan Subramaniam; Goutham Mylavarapu; Keith McConnell; Robert J. Fleck; Sally R. Shott; Raouf S. Amin; Ephraim J. Gutmark (Annals of Biomedical Engineering, 2016)

Evaluating the stationarity assumption in statistically downscaled climate projections: is past performance an indicator of future results? - Keith W. Dixon; John R. Lanzante; Mary Jo Nath; Katharine Hayhoe; Anne Stoner; Aparna Radhakrishnan; V. Balaji; Carlos F. Gaitán (Climatic Change, 2016)

Compliance Measurements of the Upper Airway in Pediatric Down Syndrome Sleep Apnea Patients - Dhananjay Radhakrishnan Subramaniam; Goutham Mylavarapu; Keith McConnell; Robert J. Fleck; Sally R. Shott; Raouf S. Amin; Ephraim J. Gutmark (Annals of Biomedical Engineering, 2016)

Effect of endophytic Bacillus sp. from selected medicinal plants on growth promotion and diosgenin production in Trigonella foenum-graecum - B. Jasim; P. R. Geethu; Jyothis Mathew; E. K. Radhakrishnan (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Influence of Probiotics on Survival, Growth, Biochemical Changes and Energy Utilization Performance of Macrobrachium rosenbergii Post-larvae - C. Seenivasan; S. Radhakrishnan; R. Shanthi; T. Muralisankar; P. Saravana Bhavan (Proceedings of the Zoological Society, 2015)

Effects of Δ9-tetrahydrocannabinol in individuals with a familial vulnerability to alcoholism - Mohini Ranganathan; R. Andrew Sewell; Michelle Carbuto; Jacqueline Elander; Ashley Schnakenberg; Rajiv Radhakrishnan; Brian Pittman; Deepak Cyril D’Souza (Psychopharmacology, 2014)

Influence of medicinal herbs (Alteranthera sessilis, Eclipta alba and Cissus quadrangularis) on growth and biochemical parameters of the freshwater prawn Macrobrachium rosenbergii - S. Radhakrishnan; P. Saravana Bhavan; C. Seenivasan; R. Shanthi; R. Poongodi (Aquaculture International, 2014)

Acute effects of THC on time perception in frequent and infrequent cannabis users - R. Andrew Sewell; Ashley Schnakenberg; Jacqueline Elander; Rajiv Radhakrishnan; Ashley Williams; Patrick D. Skosnik; Brian Pittman; Mohini Ranganathan; D. Cyril D’Souza (Psychopharmacology, 2013)

Protective role of pulsed magnetic field against salt stress effects in soybean organ culture - R. Radhakrishnan; B.D. Ranjitha Kumari (Plant Biosystems, 2013)

Identification of hot spots and well managed areas of Pichavaram mangrove using Landsat TM and Resourcesat—1 LISS IV: an example of coastal resource conservation along Tamil Nadu Coast, India - T. Srinivasa Kumar; R. S. Mahendra; Shailesh Nayak; K. Radhakrishnan; Kali C. Sahu (Journal of Coastal Conservation, 2012)

Impacts of hatchery release on genetic structure of rock carp Procypris rabaudi in the upper Yangtze River, China - Fei Cheng; Qingjiang Wu; Ming Liu; K. V. Radhakrishnan; Brian R. Murphy; Songguang Xie (Fisheries Science, 2011)

Response of west Indian coastal regions and Kavaratti lagoon to the November-2009 tropical cyclone Phyan - Antony Joseph; R. G. Prabhudesai; Prakash Mehra; V. Sanil Kumar; K. V. Radhakrishnan; Vijay Kumar; K. Ashok Kumar; Yogesh Agarwadekar; U. G. Bhat; Ryan Luis; Pradhan Rivankar; Blossom Viegas (Natural Hazards, 2011)

Identification of several small main-effect QTLs and a large number of epistatic QTLs for drought tolerance related traits in groundnut (Arachis hypogaea L.) - K. Ravi; V. Vadez; S. Isobe; R. R. Mir; Y. Guo; S. N. Nigam; M. V. C. Gowda; T. Radhakrishnan; D. J. Bertioli; S. J. Knapp; R. K. Varshney (Theoretical and Applied Genetics, 2011)

Otolith retrieval from faeces and reconstruction of prey-fish size for Great Cormorant (Phalacrocorax carbo) wintering at the East Dongting Lake National Nature Reserve, China - K. V. Radhakrishnan; Ming Liu; Wenping He; Brian R. Murphy; Songguang Xie (Environmental Biology of Fishes, 2010)

Rooting and shooting: dual function of thidiazuron in in vitro regeneration of soybean (Glycine max. L) - R. Radhakrishnan; A. Ramachandran; B. D. Ranjitha Kumari (Acta Physiologiae Plantarum, 2009)

Development and characterisation of a novel animal model of prostate inflammation-induced chronic pelvic pain - R. Radhakrishnan; R. S. Nallu (Inflammopharmacology, 2009)

Status of the major lobster fisheries in India - E.V. Radhakrishnan; V.D. Deshmukh; Mary K. Manisseri; M. Rajamani; Joe K. Kizhakudan; R. Thangaraja (New Zealand Journal of Marine and Freshwater Research, 2005)
Commercial exploitation of lobsters from the Indian seas began in the 1950s. Annual landings have been declining from a peak of 4075 t in 1985 to 1364 t in 2002. Major fisheries were located on the north‐west, south‐west, and south‐east coasts. Among the 12 species recorded, only four species of spiny lobsters (three littoral and one deep sea) and one species of slipper lobster are commercially important. At Kayalpattinam and Tharuvaikulam, on the south‐east coast, lobster landings sharply declined for the gill‐net fishery. Of the two species that contributed to the fishery, Panulirus ornatus and Panulirus homarus, the latter has been more affected owing to high vulnerability to fishing activities. Catch composition analysis of the trammel‐net fishery showed that 35% of the landings consisted of P. homarus in the size range of 23–50 mm carapace length. On the north‐west coast, the spiny lobster Panulirus polyphagus and the slipper lobster Thenus orientalis are incidentally caught in trawl nets. However, the fishery for T. orientalis in the waters off Mumbai lasted only up to 1994. Large‐scale exploitation of spawning females, which formed 60% of the total catch, might have been detrimental to the recruitment process resulting in rapid decline and total collapse of the fishery. Abundance of P. polyphagus reached its maximum during September, constituting 23% of the average annual landing during 1988–2002. A high exploitation ratio (>0.7) indicated over‐fishing of the stock. Repeated spawning and high annual egg production are probably responsible for sustaining the stock, despite over‐exploitation. Major problems confronting the resource management of the multi‐gear and multi‐species lobster fisheries in India are discussed. An operational project, involving fisher community, has been taken up for creating awareness of the need for sustainable exploitation of the resource. Regulatory measures, such as closure of the fishery during the peak of the breeding season, ban on trammel‐net, mandatory release of egg‐bearing lobsters, and establishment of lobster sanctuaries are suggested to the State Governments for implementation.

Agnoprotein and its coding sequences play regulatory roles in JC virus gene transcription and replication in glial cells - M Safak; R Biffi; S Radhakrishnan; S Woolridge; I K Sariyer; I Akan; J Gordon; S Amini; P Ferrante; K Khalili (Journal of NeuroVirology, 2004)